2019
DOI: 10.4103/jfmpc.jfmpc_290_17
|View full text |Cite
|
Sign up to set email alerts
|

Chronic musculoskeletal pain among elderly in rural Tamil Nadu: Mixed-method study

Abstract: Objectives: (1) To determine the prevalence of chronic pain of musculoskeletal origin at different body sites among elderly (≥60 years). (2) To study the determinants of chronic pain and the healthcare seeking behavior among elderly with chronic pain. (3) To explore the perceptions of chronic pain among elderly. Materials and Methods: This study was done in 55 field practice villages of the Rural Health Training Centre (RHTC) of the Department of Community Medicine, SMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Whilst acknowledging the challenges of assessing and managing chronic pain in older people, this study does indicate that evidence of the provision of appropriate integrated and person-centred care is lacking. This finding resonates with other studies in urban [21,22], and remote and rural areas [12,13] across the world. These also highlighted age as a key predictor for chronic pain and suboptimal management in older people who often report poor effectiveness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whilst acknowledging the challenges of assessing and managing chronic pain in older people, this study does indicate that evidence of the provision of appropriate integrated and person-centred care is lacking. This finding resonates with other studies in urban [21,22], and remote and rural areas [12,13] across the world. These also highlighted age as a key predictor for chronic pain and suboptimal management in older people who often report poor effectiveness.…”
Section: Discussionsupporting
confidence: 92%
“…There are acknowledged difficulties associated with the provision of, and access to, healthcare within remote and rural areas, particularly for older people [12,13]. NHS Highland is the largest geographical health board in Scotland with a population of around 310,000 (<10% of the Scottish population) and more than 40% living in 'remote rural' locations (settlements with a population <3,000 people and a drive time of >30 minutes to a settlement of ≥10,000) [14].…”
Section: Introductionmentioning
confidence: 99%
“…With the population aging, a rise in prevalence for chronic and degenerated diseases is inevitable, leading to a high incidence of chronic pain in the elderly [2,3]. Previous studies have investigated the incidence of chronic pain in the elderly, showing a prevalence ranging from 43.8 to 55.2% in elderly population residing in the east [4][5][6][7] while 40 to 66% prevalent among those in the west [8,9]. Moreover, the most common sites of pain in older people are the back, leg, knee or hip, and 'other' joints (such as joints of fingers, wrists and toes) in the most developed countries [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most common site for chronic pain was knee joint (64.5%) followed by a low backache (21.7%). 6 A cross-sectional study conducted by Mendhe HG et al (2016) in Andhra Pradesh revealed that overall prevalence of MSD was 61%. Joint pain was the most common symptom in the study participants (47.7%), 16% had joint stiffness, 19.75% had muscle pain, 20.7% had spine or back pain, and 23.25% had joint swelling.…”
Section: Resultsmentioning
confidence: 99%